Indonesia's Empowered Economy Transition: A Path to Sustainable Prosperity - Iffada, Berliana; Syafa’ati, Fiskia; Mawardi, Wisnu (Research Horizon, 2024)
Indonesia's pursuit of an empowered economy aligns with its broader goal of achieving sustainable prosperity. This transition necessitates a comprehensive approach that integrates economic, environmental, and social dimensions. A key component of this strategy is the empowerment of Indonesian citizens, particularly those in the traditional sector, to drive economic growth and reduce poverty. This study aims to provide a comprehensive overview of current research related to economic empowerment for sustainable welfare in Indonesia. The method used in this research is Systematic Literature Review, referring to various literatures published between 2015 to 2024. The results of this study show that by implementing structural reforms, optimizing natural resource management, and strengthening the industrial sector, Indonesia can build a resilient and inclusive economy. Moreover, investing in renewable energy, developing sustainable infrastructure, and fostering community empowerment are essential for realizing a sustainable future. Through a concerted effort by the government, private sector, and civil society, Indonesia can position itself as a global leader in realizing sustainable economic empowerment and prosperity.